Evaluation of the Conditions of Mamberamo River Water with Biomass and Phytoplankton Community Approach - Mirna Dwirastina; Dwi Atminarso (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
HighlightThe highest composition was Bacillariophyceae class and lowest was Cyanophyceae.Phytoplankton community abundance in waters is tightly related with nutrient content such as phosphate, nitrate, silicate, and other nutrients.Relation between abundance, biomass, and nutrients in Mamberamo river had the same pattern throughout February, May, and August in 2016.High biomass in an area related positively with phytoplankton abundance in its area.AbstractMemberamo River in Papua Province, that is a place of livelihood for the surrounding population, has a high biodiversity. This study aimed to provide information about the condition of the waters in the Mamberamo River by using biological and chemical parameters, namely community and phytoplankton biomass and chlorophyll-a content. The method used in determining the location was purposive random sampling based on differences in microhabitat that conducted in February, March, August, and October 2016. Phytoplankton observations were carried out through the method of sweeping Sediment Rafter (SR), and phytoplankton biomass obtained from chlorophyll-a. The results of this study showed three classes of phytoplankton were found, namely Bacillariophyceae, Chlorophyceae, and Cyanophyceae. The highest class of abundance was found in the river such as Bacillariophycea Chlorophyceae, and Cyanophyceae respectively. The chlorophyll-a concentration of phytoplankton biomass ranged from 2.01-548.73 mg/l and equation obtained from regression analysis between abundance and chlorophyll-a content was y = 1.2206 x – 0.7702 with a coefficient of determination r = 0.68. It could be concluded that the high phytoplankton biomass had a positive relationship with the chlorophyll-a content and the condition of the waters of the Mamberamo River is still categorized as good with good water fertility